Kajian Teknis Produksi Alat Muat dan Alat Angkut Untuk Meningkatkan Efisiensi Produksi Batubara di Block A PT. Daya Bara Nusantara - Bilhadi, Gilang Asra; Nursanto, Edy; Nusanto, Gunawan (Jurnal Rekayasa Sipil dan Lingkungan, 2023)
PT Daya Bara Nusantara is the coal company of KBPC Group, which is located in Bungo Regency, Jambi Province. The coal mining system is an open pit backfilling method with a combination of mechanical equipment to carry out mining activities to achieve a production rate of 6,000 tons per month. The mechanical equipment used in the excavation and loading activities is the Doosan 500LCV Excavator. The transportation used is a Hino500 CWB340 truck. The location is in Block A, which is transported for the purpose of stock pile transportation. The problem is not achieving the production target of 6,000 tons per month. Based on field data, production is currently at 5,588.56 tons per month. Based on the results of the study, the production capacity of the digging tool is 5,588.56 tons per month, and the conveyance capacity is 6,341.76 tons per month. The work efficiency is 59.42%, while the work efficiency for conveyance is 58.5%. Two ways were performed to increase the production of coal stripping. The first is to increase the efficiency of the tool. The increase in the work efficiency of the loading and unloading equipment is 67.9%, and the work efficiency of the hauling equipment is 66.67%. Production of digging and unloading increased to 6,386.12 tons per month, and conveyance production increased to 6,570.4 tons per month. The second is to reduce conveyance units. A mining operation that previously used 11 units was changed to 10 units of conveyance. After reducing the number of conveyance units, production from coal mining increased to 6,570.4 tons per month, with a match factor of 1. ABSTRAK Daya Bara Nusantara merupakan perusahaan batubara KBPC Group terletak di Kabupaten Bungo, Provinsi Jambi. Sistem pertambangan Batubara yaitu tambang terbuka dengan menggunakan system Back Filling dengan kombinasi alat mekanis untuk kegiatan penambangan dalam mencapai target produksi yaitu sebesar 6.000 ton/bulan. Alat mekanis penggalian dan pemuatan yaitu Excavator Doosan 500 LCV. Alat angkut yang digunakan truk Hino 500 CWB 340. Lokasi penelitian pada Block A yang diangkut di Stockpile. Permasalahan belum tercapainya target produksi 6.000 ton/bulan. Berdasarkan data di lapangan, produksi masih 5.588,56 ton/bulan. Kemampuan produksi alat gali muat 5.588,56 ton/bulan dan alat angkut 6.341,76 ton/bulan. Efisiensi kerja alat gali muat 59,42 %, sedangkan efisiensi kerja untuk alat angkut yaitu 58,5 %. Peningkatan produksi penambangan batubara dilakukan dengan cara, yaitu pertama meningkatan efisiensi kerja alat. Peningkatan efisiensi kerja alat gali muat 67,9 % dan efisiensi kerja alat angkut 66,67 %. Produksi alat gali muat meningkat 6.386,12 ton/bulan dan produksi alat angkut 6.570,4 ton/bulan. Cara kedua adalah melakukan pengurangan jumlah unit alat angkut. Pada kegiatan penambangan yang sebelumnya menggunakan 11 unit alat angkut menjadi 10 unit. Setelah pengurangan jumlah unit alat angkut, produksi yang dihasilkan dari penambangan batubara meningkat 6.570,4 ton/bulan, dengan match factor yaitu 1.